Nasopharyngeal aspiration for diagnosis of pulmonary tuberculosis. Issue 8 (21st December 2006) - Owens, S; Abdel-Rahman, I E; Balyejusa, S; Musoke, P; Cooke, R P D; Parry, C M; Coulter, J B S
Abstract : Background: Confirmation of pulmonary tuberculosis (PTB) in young children is difficult as they seldom expectorate sputum. Aim: To compare sputa obtained by nasopharyngeal aspiration and by sputum induction for staining and culture of Mycobacterium tuberculosis . Patients and methods: Patients from Mulago Hospital, Kampala with symptoms suggestive of PTB were considered for inclusion in the study. Those with a positive tuberculin test and/or a chest radiograph compatible with tuberculosis were recruited. Infection with human immunodeficiency virus (HIV) was confirmed by duplicate enzyme-labelled immunosorbent assay or in children <15 months by polymerase chain reaction (PCR). Direct PCR was undertaken on 82 nasopharyngeal aspirates. Results: Of 438 patients referred, 94 were recruited over a period of 5 months. Median (range) age was 48 (4–144) months. Of 63 patients tested, 69.8% were infected with HIV. Paired and uncontaminated culture results were available for 88 patients and smear results for 94 patients. Nasopharyngeal aspirates were smear-positive in 8.5% and culture-positive in 23.9%. Induced sputa were smear-positive in 9.6% and culture positive in 21.6%. Overall, 10.6% were smear-positive, 25.5% were culture-positive and 26.6% had smear and/or culture confirmed tuberculosis. Direct PCR on nasopharyngeal aspirates had a sensitivity of 62% and specificity of 98% for confirmation of culture-positive tuberculosis. Conclusions: Nasopharyngeal aspiration is a useful, safe and low-technology method for confirmation of PTB and, like sputum induction, can be undertaken in outpatient clinics.